Brixia Score as Predictor of D-Dimer Levels of COVID-19 Patients in Intensive Care Unit - Yanuareza Totti Adyanata; Widiastuti Soewondo; Arifin Arifin; Dhani Redhono (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: COVID-19 is caused by a novel virus that can cause lung abnormalities which can be measured with new chest x-ray scoring system named Brixia score. In COVID-19 patients, coagulation disorders are often found that can be seen through D-Dimer levels. This study aimed to prove the Brixia Score as a predictor of D-Dimer levels.Subjects and Method: This study was an observational analytic study with a cross-sectional approach. The subjects were 94 COVID-19 patients which taken from ICU Melati 1 Dr. Moewardi General Hospital, Surakarta from March 2021 to August 2021 who met the exclusion and inclusion criteria. The independent variable is the Brixia score performed by radiologists and the dependent variable is D-Dimer levels taken from laboratory results. Sampling was obtained by purposive sampling and the data were investigated using the receiver operating characteristic (ROC) curve.Results: 94 samples were obtained for analysis. The average Brixia Score of patients with D-Dimer <2 µg/mL was Mean= 15.85; SD= 1.43 and D-Dimer ≥2 µg/mL was Mean= 17.29; SD= 0.96. There was a significant difference between the Brixia Score of patients with D-Dimer <2 µg/mL and D-Dimer ≥2 µg/mL (p<0.001). Analysis with the ROC curve shows an area under the curve (AUC) of 0.793. The optimal cutoff value of the Brixia Score for predicting D-Dimer levels was 16.5 (sensitivity 77.9%, specificity 73.1%).Conclusion: Brixia Score proved to be a predictor of D-Dimer levels of COVID-19 patients in ICU care.Keywords: COVID-19, ICU, brixia score, predictor, D-Dimer.Correspondence: Widiastuti Soewondo, Radiology Department, Faculty of Medicine, Universitas Sebelas Maret. JL. Ir. Soetami No. 36A, Surakarta 57126, Indonesia. E-mail: widiastuti.sprad56@staff.uns.ac.id. Mobile: 082134368592Indonesian Journal of Medicine (2023), 08(01): 92-99https://doi.org/10.26911/theijmed.2023.08.01.09